Phase Transition Behaviors and Nanoscale Film Morphologies of Poly(δ‐valerolactone) Axles Bearing Movable and Fixed Rotaxane Wheels. Issue 21 (6th September 2019) - Ree, Brian J.; Aoki, Daisuke; Kim, Jehan; Satoh, Toshifumi; Takata, Toshikazu; Ree, Moonhor
Abstract: In this study, poly(δ‐valerolactone) (PVL) axles bearing movable and fixed dibenzo‐24‐crown‐8‐ether wheels ( rot ‐M and rot ‐F) are investigated for the first time in the terms of phase transition and nanoscale film morphology: PVL‐ rot‐ M and PVL‐ rot ‐F. Interestingly, the PVL axles reveal a strong tendency to form a horizontal lamellar structure with three different rotational crystal lattice domains in nanoscale films. The morphological structural parameters are discernibly varied by the movable and fixed rotaxane wheels. In particular, the rot ‐M wheel tends to be populated in both the interfacial and amorphous layers. The rot ‐M wheel is found to significantly influence the phase transition characteristics of the PVL axle because of its movability along the polymer backbone chain. In contrast, the rot ‐F wheel tends to be more localized in the interfacial layer rather than in the amorphous layer because of its immovability constrained at the polymer chain end. The rot ‐F wheel causes severe thermal instability in the PVL axle, which can be attributed mainly to the presence of its counter anion (PF6 − ). Abstract : Poly(δ‐valerolactone) (PVL) axles bearing movable and fixed rotaxanes ( rot ‐M and rot ‐F) are investigated in terms of phase transition and nanoscale film morphology. rot ‐M significantly influences the phase transitions of the PVL axle compared to rot ‐F. rot ‐F causes thermal instability in the PVL axle. The PVL axle forms a horizontal lamellar structure with rotational crystal lattice domains; the structural parameters are discernibly varied by the movable and fixed rotaxanes.